Automation of accounting of publications using the ORCID application programming interface - Ivanov, Serhii; Ivohin, Eugene; Makhno, Mykhailo (Visnyk Kyïvsʹkoho universytetu. Serii͡a︡--Fizyko-matematychni nauky (2009), 2024)
The procedure for automated accounting of publications based on the use of Rest API of the ORCID database is proposed. The relevance of publication accounting is described. The importance of using various technologies for creating bibliographic data repositories is substantiated. The possibility of using API technology in the most famous publication databases such as Web of science, SCOPUS, Crossref, Google Scholar, and ORCID was analyzed. The possibility of using the ORCID database is substantiated. The scheme for downloading publications from the ORCID database by specified registration numbers based on services implemented in the Python and MatLab programming languages is given. The received data in JSON or XML is subject to further parsing. MatLab functions for obtaining a structure from XML (JSON) data formats are provided.In addition, the algorithm for finding duplicate publications during their accounting is considered. Approaches to avoid duplication of publications in databases based on the application of the Levenstein algorithm for similarity assessment are formulated. It is proposed to transliterate the Cyrillic alphabet into the Latin alphabet to ensure clarity and correct comparison of textual data. A MySql database was developed to collect and update data on publishing activity. The title of the publication table of the database is supplemented with a special attribute, which stores the results of the conversion of Cyrillic names into corresponding Latin names. It is recommended to use indexing of database table fields (INDEX) by various attributes, which allowed to significantly increase the efficiency of searching, processing and comparing data. It is proposed to use the Soundex() function as a MySQL DBMS tool to determine the level of consonance of publication topics by additional parameters. The practical implementation of the algorithm for finding duplicate publications and their numbering confirmed the constructiveness of the proposed approach which was confirmed when filling the database. This article is of interest to software developers.